A study on agroforestry activities in Tana Toraja, Indonesia - Jambut, Azrihisyam; Hassan Zaki, Pakhriazad; Ismail, Mohd Hasmadi (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
The basic human needs of food, shelter and fuel are often supplied by separate systems of land management. Building material and fuelwood are harvested from forests and food is produced from fields of herbaceous crops, fruit orchards and livestock grazing in pastures. Agroforestry is a land use management system in which trees are mixed in the same land with food crops or pasture for domestic animals. This study was conducted to examine the agroforestry activities and to examine monetary values of goods collected by selected village communities in Tana Toraja, South Sulawesi, Indonesia. The local government seat of Tana Toraja is in Makale, which comprises 47 sub-districts with 112 villages adjacent to Toraja Utara District and West Sulawesi Province in the north, Enrekang and Pinrang District in the south, Luwu District in the east, and West Sulawesi Province in the west. Monetary value of various agriculture and non-timber forest products (NTFPs) collected from the forest and the product cultivated and harvested from forestlands have been evaluated. Primary and secondary data were collected. Primary data consists of in-depth interviews, questionnaires distributed to selected 250 respondents, and site observations. Secondary data was collected through literature review through journals, articles and official government documents. Data collection was analyzed using Chi square test and SPSS. The multiple regression analysis was applied to develop agroforestry dependency model for the selected villages. This study revealed that more than half of the respondents were involved in agricultural and forest related activities, which is eighty-one percent. The highest income range is RM 901.00- RM1,200.00 (Rp 3,0M – Rp 4,0M). The Tana Toraja community heavily depends on agricultural and agroforestry related activities as their major source of income.